Assessment of Knowledge and Perception of Sodium-Glucose Co-transporter 2 (SGLT-2) Inhibitors Prescription among Physicians in Saudi Arabia - Somaili, Mohammed; Oraibia, Omar; Darraj, Majed; Hassan, Amal; Moafa, Esaam; Kulaybi, Abdulrahman; Shubayli, Sahar; Moafa, Razan; Mghfori, Ghadah; Jaafari, Afaf; Somily, Majed (Current Diabetes Reviews, 2024)
Background: Sodium-glucose cotransporter 2 inhibitors are a new class of medications that have been proven to improve both glycemic control and cardio-renal outcomes. The knowledge, attitude, and perception toward their prescriptions in Jazan, Saudi Arabia, are still unknown. Objective: The study aimed to measure the level of knowledge and attitude toward sodium-glucose cotransporter 2 inhibitors prescription among physicians in the Jazan region, Saudi Arabia. Methods: Data analysis was performed using Statistical Package for the Social Sciences, SPSS 23rd version. Frequency and percentages were used to display categorical variables. Minimum, maximum, mean, and standard deviation were used to test numerical variables. Independent t-test and ANOVA test were both utilized to test the factors associated with knowledge and attitude toward the use of SGLT-2 inhibitors. Results: A total of 65 participants were included in the study. 26.2% had a low knowledge level, 30.8% had a moderate knowledge level, and 43.1% had a high knowledge level of sodium-glucose cotransporter 2 inhibitors. 9.2% had a low attitude level, 43.1% had a moderate attitude level, and 47.7% had a high attitude level toward sodium-glucose cotransporter 2 inhibitors. Age, professional status, years of experience, and specialty were significantly associated with attitude but not with the knowledge of sodium-glucose cotransporter 2 inhibitors prescription. Conclusion: While the study cohort scored high in the knowledge and attitude domains of the survey, a large proportion failed to answer very essential questions in type 2 diabetes management. An educational awareness program needs to be carried out to strengthen the physicians’ knowledge of SGLT2 inhibitors prescription.
Keywords: type 2 diabetes mellitus